Effect of Guizhou red sour soup on lipid metabolism in rats fed a high-fat diet - HU Shiyao, YUAN Qin, ZHENG Yuancui, WANG Huiqun (Zhongguo niangzao)
In order to explore the effect of Guizhou red sour soup on lipid metabolism in high-fat diet rats and its mechanism, using specific pathogen- free (SPF) SD male rats as experimental subjects and randomly divided into three groups for 12 weeks of continuous intervention. The body and liver mass of the rats were weighed, the body mass index (BMI) and liver index (LI) were calculated, the serum lipid level was detected, and the histopathological changes of the liver were observed. The expression levels of leukocyte differentiation antigen 36 (CD36), fatty acid transporter 4 (FATP4), peroxisome proliferator-activated receptor α (PPARα) and carnitine palmitoyl transferase 1 (CPT1) in liver were determined. The results showed that Guizhou red sour soup could reduce the body mass, body mass index and liver index of high-fat diet rats, reduce the levels of triglyceride (TG), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) in serum, and increase the level of high-density lipoprotein cholesterol (HDL-C). At the same time, Guizhou red sour soup could inhibit the expression of FATP4 and CD36 in the liver of high-fat diet rats, and promote the expression of PPARα and CPT1. The results showed that Guizhou red sour soup could prevent the occurrence of obesity in rats with high fat diet, improve blood lipid level and liver steatosis. The mechanism of its action might be that it inhibited fatty acid uptake and transport in hepatocytes and promoted the β-oxidation of fatty acid in hepatocytes, thus improving the disorder of lipid metabolism in rats.